Nano composite biological material based on cuttlefish ink and copper oxide and used for treating tumor cells
By developing a nanocomposite biomaterial of cuttlefish juice@copper oxide (M@CuO), which has good photothermal conversion performance under near-infrared light irradiation and exhibits good Fenton effect at room temperature, the photothermal therapy is solved The deficiency of chemokinetic therapy has achieved efficient combined photothermal-chemokinetic therapy.
Patent Information
- Application Number
- CN202411477961.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-22
AI Technical Summary
Existing photothermal therapy and chemokinetic therapy are insufficient for tumor depth and recurrence, especially the biological tissue penetration of photothermal therapy and the therapeutic effect stops immediately after the excitation light stops, Fenton response rate of chemokinetic therapy Slower, resulting in poor efficacy.
Develop a nanocomposite biomaterial of cuttlefish juice @ copper oxide (M@CuO) that has good photothermal conversion performance under near infrared light irradiation and exhibits good Fenton effect at room temperature and Fenton reaction rate It can be further improved by the photothermal effect.
It has achieved efficient killing of tumor cells under combined photothermal-chemodynamic therapy, providing a long-term tumor treatment strategy that can effectively inhibit tumor recurrence.
Smart Images

Figure CN119405800A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a nano composite biomaterial, in particular to a nano composite biomaterial based on cuttlefish juice@copper oxide, and the nano composite biomaterial is used for treating tumor cells or degrading dyes. Background Art
[0002] Cancer seriously threatens people's life safety and health due to its high morbidity and mortality. In order to effectively treat cancer, a variety of new treatment strategies have been developed in recent years. These treatment methods mainly include: photodynamic therapy (PDT), photothermal therapy (PTT), sonodynamic therapy (SDT) and chemodynamic therapy (CDT). However, although each treatment method has its unique advantages, it also has some shortcomings. For example, PTT mainly uses near-infrared (NIR) light to generate heat to cause cancer cell death, but NIR light has weak biological tissue penetration and can only treat superficial cancer cells. When the excitation light stops irradiation, the PTT effect will also stop immediately, and the tumor cannot be suppressed for a long time, and the tumor is prone to recurrence. In addition, the complexity and diversity of tumors further limit the effect of single treatment based on nanomedicine, resulting in the current trend of clinical research on tumors to shift from single treatment to comprehensive synergistic treatment to improve the overall efficacy.
[0003] In order to make up for the shortcomings of single photothermal therapy, our research group has recently developed a cuttlefish juice-protoporphyrin nanocomposite (CIPs), which can effectively treat tumor cells with PTT-SDT combined treatment. In the SDT treatment mode, the tissue penetration depth of ultrasound is large (>10 cm), which can effectively treat deep tumors; but there is also a problem that the treatment effect stops immediately after the ultrasound excitation stops, and the tumor is prone to recurrence. CDT uses the nanomaterial itself to react with H2O2 in the tumor microenvironment to generate highly toxic hydroxyl radicals (•OH) to kill tumor cells. This treatment method can not only treat deep tumor cells, but also produce chemokinetic effects for a long time; but the rate of CDT producing •OH through Fenton reaction is slow, resulting in unsatisfactory efficacy of CDT. When PTT and CDT are used together, not only can their respective shortcomings be compensated, but the temperature can also be increased through PTT to accelerate the rate of generating •OH through Fenton reaction, thereby enhancing the therapeutic effect of CDT. The key to PTT-CDT combined treatment is to develop multifunctional nanomaterials with significant photothermal conversion performance and chemokinetic effects. Summary of the invention
[0004] In view of the above technical problems, the present invention provides a nanomaterial with photothermal-chemodynamic therapy (PTT-CDT) function. The core of the nanomaterial is squid juice (M), and a layer of CuO is grown on the outside of the nanomaterial to successfully construct a M@CuO composite multifunctional nanomaterial. The M@CuO composite material is nano-spherical and has good photothermal conversion performance (η T =47% or more). In addition, M@CuO exhibits a good Fenton effect at room temperature (25°C), and the Fenton reaction rate can be further increased by the photothermal effect. Under the same conditions, the Fenton reaction rate at 45°C is more than twice that at 25°C. In in vitro cell experiments, M@CuO shows good biosafety and can efficiently kill tumor cells under the combined photothermal-chemodynamic therapy effect, providing an effective strategy for the development of multifunctional nanomaterials with PTT-CDT combined therapy.
[0005] The technical solution of the present invention provides a nanocomposite biomaterial based on cuttlefish ink@copper oxide. The composite biomaterial is a M@CuO composite multifunctional nanomaterial constructed with cuttlefish ink as the core and a layer of CuO grown on the outside. The M@CuO composite material is spherical, with a nanoparticle size of 100-130 nm and a surface potential of -8~-10 mV.
[0006] Another aspect of the present invention provides a method for preparing a nano-composite biomaterial based on cuttlefish ink@copper oxide for the above-mentioned composite material, comprising the following steps: adjusting the pH value of the ink sac of fresh cuttlefish to 12-13, stirring for 12-20 hours and then centrifuging, adding the nanoparticles obtained after centrifugation to a CuSO4 solution, magnetically stirring for 3-5 minutes, filtering, drying, and calcining to obtain black particles, namely, cuttlefish ink@copper oxide composite nanomaterial (M@CuO).
[0007] In the method, any one solution of sodium hydroxide, potassium hydroxide, sodium methoxide and potassium methoxide is used to adjust the pH value to 12-13.
[0008] The concentration of the CuSO4 solution is 0.01-0.2 mol·L -1 ; The concentration of the CuSO4 solution is any value within its range.
[0009] The calcination temperature is 350-500°C, and the calcination time is 3-5h. The calcination temperature and calcination time are any values within the range.
[0010] Another technical solution of the present invention is to provide a photothermal material and / or a specific Fenton effect material, wherein the photothermal material and / or the specific Fenton effect material is the cuttlefish ink@copper oxide nanocomposite biomaterial or the cuttlefish ink@copper oxide nanocomposite biomaterial prepared by the method.
[0011] As a photothermal material, the cuttlefish juice@copper oxide nanocomposite biomaterial achieves a temperature increase effect under 800-850nm near-infrared laser irradiation, and the concentration of the cuttlefish juice-porphyrin nanoconjugate is 0.025-0.4mg mL -1 ; and / or, As a specific Fenton effect material, it is a material that catalyzes H2O2 to generate •OH through the Fenton reaction.
[0012] Another technical solution of the present invention is to use the cuttlefish juice@copper oxide nanocomposite biomaterial or the cuttlefish juice@copper oxide nanocomposite biomaterial prepared by the method in the preparation of a drug for treating tumor cells, wherein the tumor cells include cancer cells 4T1.
[0013] The cuttlefish juice@copper oxide nanocomposite material is used to achieve in vitro photodynamic-photothermal combined treatment of tumor cells through tumor photothermal-chemodynamic combination.
[0014] The technical solution of the present invention also provides a photocatalytic agent for degrading dyes, wherein the photocatalytic agent is the cuttlefish ink@copper oxide nanocomposite biomaterial or the cuttlefish ink@copper oxide nanocomposite material prepared by the method.
[0015] The dye object described in the present invention includes any one of MB, rhodamine B, and orange red II.
[0016] In the technical solution of the present invention, the dosage of the photocatalytic agent for degrading the dye is 0.01-0.5 mg·mL -1 ; preferably 0.05-0.2 mg·mL -1 ; More preferably, 0.1 mg·mL -1 .
[0017] In the technical solution of the present invention, cuttlefish juice is mainly amorphous carbon composed of elements such as C, N, and O, and the surface contains rich -OH, -C=O-, -C=C- and other groups. Cuttlefish juice is considered to be an excellent photothermal reagent due to its natural biocompatibility and biodegradability. In addition, copper-based nanomaterials have been proven to be effective Fenton reagents, and the copper-catalyzed Fenton reaction has a higher catalytic efficiency under weakly acidic and neutral conditions, which is 160 times the rate of the Fenton reaction mediated by iron-based nanomaterials. Therefore, the present invention constructs a multifunctional cuttlefish juice@copper oxide composite nanomaterial (M@CuO) for cancer cell treatment. The results of the study show that M@CuO not only has good PTT and CDT effects, but also the CDT performance can be further significantly improved through the PTT effect, thereby achieving an efficient PTT-CDT combined therapeutic effect ( Figure 1 ).
[0018] The present invention successfully prepared a multifunctional M@CuO composite nanomaterial for combined photothermal-chemodynamic therapy (PTT-CDT) of tumors. M@CuO has a spherical structure with a particle size of 128.2 nm, which is slightly larger than the nanometer diameter of pure cuttlefish juice (105.6 nm). M@CuO still exhibits good near-infrared light absorption and good photothermal conversion efficiency (η T =47.6%). In addition, M@CuO exhibits Fenton reaction characteristics (25°C), and the reaction rate can be further significantly increased (2.3 times) by photothermal effect (45°C). Co-incubation of M@CuO dispersion with cells showed good biosafety, and tumor cells could be efficiently killed under the combined photothermal-chemodynamic therapy effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 . Synthesis route of M@CuO and its application in combined photothermal-chemodynamic therapy of tumor cells.
[0020] Figure 2 . (a,b) SEM images and particle size distribution of M. (c,d) SEM images and particle size distribution of M@CuO.
[0021] Figure 3 . XRD pattern (a), X-ray photoelectron spectroscopy (b, c) and UV-visible-near-infrared absorption pattern (d) of M@CuO.
[0022] Figure 4. (a) Temperature variation of M@CuO dispersions with different concentrations under 808 nm laser irradiation. (b) Photothermal cycle stability diagram of M@CuO dispersion. (c) Temperature variation curve of M@CuO dispersion under laser on / off state. (d) Linear fitting of M@CuO linear time data to -ln(θ).
[0023] Figure 5 (a) Schematic diagram of photothermal enhanced chemodynamic therapy. (b, c) Time-dependent absorption spectra of MB mediated by M@CuO and H2O2 at 25℃ or 45℃. (d) Degradation rate of MB under different conditions.
[0024] Figure 6 . (ac) Cell viability of HUVEC, CT26, and 4T1 cells after co-culture with different concentrations of M@CuO for 24 h.
[0025] Figure 7 (a) Cell viability of PTT at different illumination times. (b) Cell viability of CDT at different M@CuO concentrations.
[0026] Figure 8 .Relative survival rate (a) and fluorescence images (b) of 4T1 cells after different treatments.
[0027] Fig. 9 This is the relationship curve between temperature change (ΔT) and concentration.
[0028] Fig.10 Thermal images of M@CuO dispersions with different concentrations under 808 nm laser irradiation. DETAILED DESCRIPTION
[0029] Experimental Materials Cupric chloride dihydrate (CuCl2·2H2O), analytical grade, Shanghai MacLean Biochemical Technology Co., Ltd.; sodium hydroxide (NaOH), analytical grade, Sinopharm Chemical Reagent Co., Ltd.; polyvinyl pyrrolidone (PVP-K30), analytical grade, Shanghai MacLean Biochemical Technology Co., Ltd.; methylene blue (MB), analytical grade, Shanghai MacLean Biochemical Technology Co., Ltd.; ethanol (CH3CH2OH), analytical grade, Shanghai Aladdin Biochemical Technology Co., Ltd.; 4',6-diamidino-2-phenylindole (DAPI), analytical grade, Shanghai MacLean Biochemical Technology Co., Ltd.; phosphate buffered saline (PBS), analytical grade, Shanghai MacLean Biochemical Technology Co., Ltd.; 2′,7′-dichlorofluorescein diacetate (DCFH-DA), analytical grade, Shanghai MacLean Biochemical Technology Co., Ltd.; methylthiazolyl blue tetrazolyl (MTT), analytical grade, Shanghai MacLean Biochemical Technology Co., Ltd.
[0030] Example 1 Synthesis steps of squid ink @CuO Cuttlefish ink (M) was obtained from the ink sac of fresh cuttlefish after washing and centrifugation. Then 5 mg of M was added to a NaOH solution (5 mL, pH = 12) and stirred for 12 h. The nanoparticles after centrifugation were then added to a CuSO4 solution (5 mL, 0.1 mol·L -1 ), magnetically stirred for 5 min, filtered, dried, and finally calcined at 350 °C for 5 h. The obtained black particles were cuttlefish juice@copper oxide composite nanomaterials (M@CuO).
[0031] Material characterization of M@CuO First, the morphology and size of the composite material M@CuO were characterized. Scanning electron microscope images (SEM) showed that the cuttlefish ink (M) extracted from the ink sac of fresh cuttlefish was spherical with uniform particle size and a nanometer diameter of about 105.6 ± 2.3 nm ( Figure 2 a and 2b). After forming the composite material M@CuO, it still has a spherical structure with a particle size of 128.2±1.9 nm, which is slightly larger than the nanodiameter of pure cuttlefish ink. This may be due to the formation of CuO on the surface of M, which increases the nanodiameter ( Figure 2 c and 2d). Subsequently, the hydrodynamic size and Zeta potential of M and M@CuO nanomaterials were further measured. The results showed that the hydrodynamic diameter of M was 259.7 nm and the surface potential was -17.6 mV; while the hydrodynamic diameter of M@CuO was 289.3 nm and the surface potential was -9.7 mV, which was also due to the formation of CuO on the surface of M, which increased the nanodiameter and reduced the surface potential ( Figure 2 e and 2f). In summary, the composite material M@CuO is still spherical, but the nanodiameter is slightly increased compared with M.
[0032] Subsequently, X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) were used to further study the material composition and structure of the composite nanomaterial M@CuO. XRD results showed that M@CuO exhibited strong characteristic diffraction peaks at 35.4°, 38.5°, 48.7°, 66.4°, and 68.1°, which were consistent with the standard XRD card peaks of CuO (PDF 44-0706), indicating that a layer of CuO ( Figure 3 a). The XPS spectrum shows strong signals from C, Cu and O elements, where C comes from squid ink, and Cu and O come from CuO on the surface ( Figure 3 b). The Cu 2p spectrum shows two peaks at around 955.4 and 935.3 eV, which correspond to Cu 2+In addition, the three peaks near 963.2, 944.5 and 940.5 eV are characteristic peaks of +2-valent Cu salts ( Figure 3 c). Therefore, the Cu element in the M@CuO sample is +2 valence, which is consistent with the corresponding chemical formula result in XRD. Finally, the optical properties of M and M@CuO were measured by UV-Vis-NIR spectroscopy. The results showed that M@CuO exhibited strong light absorption at 400 ~ 1000 nm. It is worth noting that compared with pure M, the light absorption of M@CuO in the near-infrared part (800-1000 nm) is the same as that of M, indicating that the formation of the composite material M@CuO does not affect the light absorption effect of M in the near-infrared ( Figure 3 d). Therefore, we subsequently used 808 nm laser to study its photothermal performance.
[0033] Example 2 Photothermal performance test Photothermal conversion performance test: First, prepare different concentrations (0, 0.05, 0.1, 0.2, 0.4 mg mL -1 ) of the M@CuO aqueous dispersion prepared in Example 1, and then irradiated with an 808 nm laser (1.0 W·cm -2 ) are aimed at M@CuO dispersions with different concentrations and the temperature change of the dispersion is monitored using a thermal imaging camera.
[0034] Photostability test: 808 nm laser on-off 4 times (20 min / time) irradiation concentration of 0.1 mg·mL -1 The M@CuO dispersion was measured and the temperature change of the dispersion during 4 cycles was monitored using a thermal imaging camera.
[0035] Photothermal conversion performance and photothermal enhancement of chemical kinetics of M@CuO Firstly, the dispersion of M@CuO with different concentrations (0, 0.05, 0.1, 0.2, 0.4 mg·mL) was studied. -1 ) under 808 nm laser irradiation (1.0 W cm -2 ) when the light-to-heat conversion performance. Figure 4 As can be seen in a, the temperature increase effect of M@CuO dispersion under light is concentration-dependent. Pure water only increases in temperature by 3.9°C within 10 min, while M@CuO (0.4 mg·mL -1 ) increased by 62.5°C within 10 min, indicating that the M@CuO dispersion has good photothermal conversion performance under 808 nm laser irradiation ( Fig. 9 , 10). In addition, the concentration was 0.1 mg mL -1The M@CuO dispersion was placed under different laser powers (0.2-1 W·cm -2 ), and monitor its temperature change diagram. The results show that with the increase of power, the heating effect of M@CuO dispersion becomes more and more obvious, and ΔT increases from 0.2 W·cm -2 3.4°C at 1 W·cm -2 The equilibrium temperature of the M@CuO dispersion was 38.3°C at 808 nm, indicating that the M@CuO dispersion has not only concentration-dependent photothermal properties but also laser power-dependent photothermal properties. Moreover, the equilibrium temperature of the M@CuO dispersion did not change significantly after four 808 nm laser on / off cycles, showing excellent photothermal cycle stability ( Figure 4 b). Finally, the photothermal conversion efficiency of M@CuO was studied by linear fitting the data points of the M@CuO dispersion during the temperature rise / fall process ( Figure 4 c and 4d). M@CuO dispersion (0.1 mg·mL -1 ) was subjected to 808 nm laser (1 W·cm -2 ) 600 s to reach equilibrium temperature (T max =55.8°C, then the laser is turned off and the temperature drops to the initial temperature (T sur =27.6°C). The photothermal conversion efficiency of M@CuO (η T ) is 47.6%. In summary, M@CuO has excellent photothermal conversion performance and can be used as a potential photothermal material for tumor treatment.
[0036] Example 3 Hydroxyl radical (•OH) detection Prepare 90 mL of 0.005 mg mL -1 The mixed solution was stirred for 30 min in dark conditions to reach adsorption-desorption equilibrium. Subsequently, the mixed solution (M@CuO + MB) was evenly divided into three equal parts and divided into three test groups: (1) M@CuO + MB (25℃); (2) M@CuO + MB + H2O2 (25℃); (3) M@CuO + MB + H2O2 (45℃). Equal amounts of H2O2 were added to (2) and (3) in batches, and the UV-visible absorption spectra were tested at intervals of 5 min each time using a UV-visible spectrophotometer and recorded at 650 nm.
[0037] It is well known that the Cu element can catalyze H2O2 to generate highly active •OH through the Fenton reaction. When the temperature is increased, the proportion of active H2O2 molecules will increase, increasing the Fenton reaction rate and producing more •OH ( Figure 5 a). In this paper, the photothermal enhanced Fenton reaction rate of M@CuO was studied by methylene blue (MB) colorimetry. First, a solution containing M@CuO (100 μg·mL -1 ) and MB (0.005 mg mL -1 ) was stirred continuously for 30 min in the dark to reach adsorption-desorption equilibrium. Subsequently, H2O2 was added to the mixture (M@CuO + MB) after adsorption-desorption equilibrium to study the Fenton reaction rate under different conditions. Without the addition of H2O2, the characteristic absorption peak of MB in the mixture (adsorption-desorption equilibrium) did not change at all, indicating that pure M@CuO did not have the ability to produce •OH. However, when H2O2 was added at room temperature (25°C), the absorbance of the characteristic absorption peak of MB in the mixture slowly decreased from 1.64 to 1.17 ( Figure 5 b), indicating that M@CuO can effectively catalyze H2O2 to generate •OH at room temperature. For comparison, the Fenton reaction with the same concentration / reaction time was carried out under 45°C water bath conditions (simulating the photothermal heating effect). The results showed that the characteristic absorption peak absorbance of MB in the mixture dropped rapidly from 1.64 to 0.55 within 30 min ( Figure 5 c), indicating that M@CuO can continuously and efficiently catalyze H2O2 to generate •OH at 45°C. According to calculations, under the same conditions, the efficiency of MB degradation of the mixture M@CuO + MB + H2O2 at 45°C is 66.5%, which is 2.3 times that at 25°C (28.7%) ( Figure 5 d). Therefore, M@CuO can effectively catalyze H2O2 to generate •OH, which can be further enhanced by the photothermal effect.
[0038] Example 4 Cytotoxicity test Human umbilical vein endothelial cells (HUVEC), mouse colon cancer cells (CT26), and mouse breast cancer cells (4T1) were cultured at 1 × 10 4 / well were inoculated in a 96-well plate and incubated for 12 h, and then the old culture medium was replaced with a fresh culture medium containing a series of different concentrations of M@CuO NPs prepared in Example 1. After further incubation for 24 or 48 h, the cells were washed with phosphate buffered saline (PBS) and the cell viability was evaluated using the standard MTT method.
[0039] In vitro cell experiments Good biocompatibility is a prerequisite for the application of bionanomaterials. To this end, human umbilical vein endothelial cells (HUVEC), mouse colon cancer cells (CT26), and mouse breast cancer cells (4T1) were incubated with M@CuO containing different concentrations (0-400 μg·mL -1 ) to assess their cytocompatibility ( Figure 6 a, 6b and 6c). The results showed that after 24 h of co-incubation, non-cancer cell HUVEC and cancer cells CT26 and 4T1 cultured with M@CuO showed a high level of cell survival rate (>85%), indicating that M@CuO has good biosafety for cells in vitro.
[0040] Example 5 In vitro treatment Cell photothermal therapy (PTT): First, a 96-well plate containing 0.2 mg mL -1 The fresh culture medium of M@CuO prepared in Example 1 was co-incubated for 4 h. Then, the cells were irradiated with NIR light (808 nm) for different times to perform photothermal therapy of tumor cells. Finally, the survival rate of cells after photothermal therapy was evaluated by using the standard methyl tetrazolium blue (MTT) method, and the treated cells were co-stained using the Calcine-AM / PI staining method, and cell fluorescence images were taken.
[0041] Cell chemodynamic therapy (CDT): Two 96-well plates with cultured cells were washed with PBS and the old culture medium was discarded. One plate was washed with fresh culture medium containing different concentrations of M@CuO (0-0.2 mg·mL -1 , 150 μL). Another plate was replaced with fresh culture medium containing different concentrations of M@CuO (0-0.2 mg mL -1 , 150 μL) and H2O2 (100 μM) were used instead. After the two 96-well plates were placed in a cell culture incubator for 12 h, the old culture medium was discarded and the cell viability was tested by the MTT method. In addition, the cells were co-stained using the Calcine-AM / PI staining method and fluorescent images were taken.
[0042] Then, 4T1 cells were incubated with M@CuO (200 μg mL -1 ) for 12 h, and then the PTT effect under light conditions was tested using a cell viability assay kit (MTT). -2), after 3 min, the cells still showed a high survival rate (87.4%), but with the increase of illumination time, the cell survival rate gradually decreased to 41.3% (6 min) and 16.1% (9 min), indicating that M@CuO has a good PTT effect under NIR light irradiation conditions, and the target effect can be achieved by adjusting the illumination time (Figure 7a). In addition, the anticancer effect of different concentrations of M@CuO in in vitro chemodynamic therapy was studied by MTT assay. Obviously, when 4T1 cells were incubated with M@CuO for 12 h, at a given concentration (0-200 μg·mL -1 ) range, the cell viability was more than 85%. On the contrary, when the cells were incubated with M@CuO + H2O2 for 12 h, the cell viability increased from 0 μg·mL -1 100% of the concentration was reduced to 200 μg·mL -1 This indicates that the combination of M@CuO and H2O2 has a good CDT effect, and the CDT effect is dose-dependent ( Figure 7 b).
[0043] In vitro combined cell therapy: 4T1 cells were seeded in multiple 96-well plates (1×10 4 cells / well) and cultured for 12 h. Subsequently, the cultured cells were randomly divided into 7 groups: (1) Control group, (2) M@CuO group, (3) near-infrared light (NIR) irradiation group, (4) H2O2 group, (5) M@CuO + NIR, (6) M@CuO + H2O2, and (7) M@CuO + H2O2 + NIR. After different treatments, the cells were washed with PBS, and the cell viability was evaluated by the standard MTT method. In addition, the cells were co-stained with Calcein-AM / PI, and then the fluorescence images were captured using a fluorescence microscope.
[0044] To evaluate the effect of photothermal-chemodynamic combined therapy in vitro, a 200 μg mL -1 ) in DMEM medium for 12 h, and some groups were irradiated with 808 nm laser (1 W·cm −2 , 6 min) and / or H2O2 (100 μM) was added. These cells were divided into 7 groups, including: (1) Control group, (2) M@CuO group, (3) near-infrared light (NIR) irradiation group, (4) H2O2 group, (5) M@CuO + NIR group, (6) M@CuO + H2O2 group, and (7) M@CuO + H2O2 + NIR group. The cell viability of these groups was detected by MTT method and the cell fluorescence staining photos were observed by fluorescence microscopy ( Figure 8). In groups (1-4), the cell survival rates were all over 85%, indicating that the use of M@CuO, NIR or H2O2 alone had no killing effect on cancer cell 4T1. However, the cell survival rate of group (5) cells was 41.3%, indicating that M@CuO had a good PTT effect under NIR light irradiation. In addition, the cell survival rate of group (6) cells decreased to 52.8%, confirming the good CDT effect. More importantly, group (7) had the lowest cell survival rate of only 19.2%, which was attributed to the good synergistic PTT-CDT treatment effect ( Figure 8 a). At the same time, the fluorescence photos showed that the cells in groups (1-4) were almost all green fluorescent (living cells). Compared with groups (1-4), the green fluorescent area of cells in groups (5-7) decreased, while the red fluorescent area (dead cells) increased rapidly, indicating that the survival rate of cancer cells decreased. In particular, the M@CuO +H2O2+ NIR group (7) showed red fluorescence of most dead cells ( Figure 8 b). In summary, M@CuO combined with NIR light and H2O2 has excellent photothermal-chemodynamic combined therapeutic efficacy and can kill tumor cells efficiently.
Claims
1. A nanocomposite material based on cuttlefish ink@copper oxide, characterized in that: The composite material is a composite material with cuttlefish ink as the core and a layer of CuO grown on the outside to construct a M@CuO composite multifunctional nanomaterial. The M@CuO composite material is spherical, with a nanoparticle size of 100-130 nm and a surface potential of -8~-10 mV.
2. A method for preparing a nanocomposite biomaterial based on cuttlefish juice@copper oxide, characterized in that: The method comprises the following steps: adjusting the pH value of cuttlefish juice of fresh cuttlefish to 12-13, stirring for 12-20 hours and then centrifuging, adding the nanoparticles obtained after centrifugation to a CuSO4 solution, magnetically stirring for 3-5 minutes, filtering, drying, and calcining to obtain black particles, namely cuttlefish juice@copper oxide composite nanomaterials (M@CuO).
3. The method for preparing the nanocomposite material based on cuttlefish ink@copper oxide according to claim 2, characterized in that: The pH value is adjusted to 12-13 using any one solution of sodium hydroxide, potassium hydroxide, sodium methoxide and potassium methoxide.
4. The method for preparing the nanocomposite biomaterial based on cuttlefish juice@copper oxide according to claim 2, characterized in that: The concentration of the CuSO4 solution is 0.01-0.2 mol·L -1 .
5. The method for preparing the nanocomposite biomaterial based on cuttlefish juice@copper oxide according to claim 2, characterized in that: The calcination temperature is 350-500° C., and the calcination time is 3-5 hours.
6. A photothermal material and / or a material with a specific Fenton effect, characterized in that: The photothermal material and / or the specific Fenton effect material is the cuttlefish ink@copper oxide nanocomposite material according to claim 1 or the cuttlefish ink@copper oxide nanocomposite material prepared by the method according to any one of claims 2-5.
7. The photothermal material and / or the material with specific Fenton effect according to claim 6, characterized in that: As a photothermal material, the cuttlefish juice@copper oxide nanocomposite material achieves a temperature increase effect under 800-850nm near-infrared laser irradiation, and the concentration of the cuttlefish juice-porphyrin nanoconjugate is 0.025-0.4 mg mL -1 ; and / or, As a specific Fenton effect material, it is a material that catalyzes H2O2 to generate •OH through the Fenton reaction.
8. Use of the cuttlefish ink@copper oxide nanocomposite material according to claim 1 or the cuttlefish ink@copper oxide nanocomposite material prepared by the method according to any one of claims 2 to 5 in the preparation of a drug for treating anti-tumor cells, characterized in that: The tumor cells include cancer cells CT26 and 4T1.
9. The use according to claim 8, characterized in that: The cuttlefish juice@copper oxide nanocomposite biomaterial is used to achieve in vitro photodynamic-photothermal combined treatment of tumor cells through tumor photothermal-chemodynamic combination.
10. A photocatalytic agent for degrading dyes, characterized in that: The photocatalytic agent is the cuttlefish juice@copper oxide nanocomposite biomaterial according to claim 1 or the cuttlefish juice@copper oxide nanocomposite biomaterial prepared by the method according to any one of claims 2-5.
Citation Information
Patent Citations
Multi-enzyme active metal-based cuttlefish ink melanin composite material and preparation method thereof
CN114433243A
Cuttlefish ink chelated iron nanoparticles as well as preparation method and application thereof
CN115054688A
MXene-cuttlefish ink melanin compound with photo-thermal synergetic antibacterial performance and preparation method and application of MXene-cuttlefish ink melanin compound
CN115531537A
Injectable photothermal hydrogel based on melanin, preparation method, and application thereof
US12102682B1
Treatment of pigmented tissues using optical energy
US7036516B1
Cited By
Device and method for treating long-carbon-chain polyalkyl flotation agent in salt lake potassium salt extraction industrial wastewater
CN120647077A